Protecting Plant Stands: Peanut Industry Moves Quickly to Address Emerging Disease Threat. Issue 3 (3rd May 2021) - Brenneman, Tim
Abstract: Uniform stands of 4 plants/ft are recommended for runner peanuts to obtain maximum yield and manage stand‐sensitive diseases such as tomato spotted wilt virus that can cause serious crop loss. Numerous seed‐ and soil‐borne diseases can threaten stands if not controlled. With increasing heat and drought stress, such as experienced in 2019, Aspergillus is of particular concern. Seed treatment fungicides are the first line of defense, but the unexpected development of resistance to a key fungicide class (QoIs) just prior to planting in 2020 caused the industry to rapidly alter its standard programs. Another major industry change is a shift from dust formulations to a liquid polymer delivery system. Earn 0.5 CEUs in Integrated Pest Management by reading the article and taking the quiz at www.certifiedcropadviser.org/education/classroom/classes/980 .